Systematic Review of Investment Risks and Stock Returns: Evidence on ESG, Policy Uncertainty, and Institutional Behavior - Nadila, Nadila; Panggeso, Anastasia Gloria; Syarifuddin, Syarifuddin; Darmawati, Darmawati (Economics, Business, Accounting & Society Review, 2025)
Investment in capital markets is inherently exposed to various forms of risks, which directly impact stock returns. Understanding the relationship between risk and return is crucial for investors aiming to make informed decisions. This study aims to explore how investment risks—particularly those related to climate policy uncertainty, macroeconomic instability, and environmental conditions—affect stock returns, and to assess whether institutional investors can mitigate such impacts. To address these objectives, this research adopts a Systematic Literature Review (SLR) methodology, synthesizing findings from high-impact journals indexed in Scopus. The analysis reveals that economic policy uncertainty and environmental degradation significantly increase market volatility, especially in sectors sensitive to regulation such as energy, finance, and real estate. Additionally, institutional investors—due to their analytical capacity, access to information, and diversification strategies—are shown to reduce the adverse effects of investment risk on portfolio performance. Furthermore, ESG factors and investor behavior, including herding and sentiment dynamics, play an increasingly critical role in shaping risk-return profiles. The study highlights the importance of integrating risk indicators such as macroeconomic variables, ESG metrics, and policy uncertainty into predictive return models. These findings offer actionable insights for investors and policymakers seeking to optimize investment strategies under uncertainty. By clarifying the link between investment risk and stock returns, this research contributes to a deeper understanding of risk management in emerging and developed markets alike.